Mechanisms of hematogenous tumor metastasis. - V. I. Desyaterik; Y. S. Shevchenko (Medičnì Perspektivi)
Metastasis is the most common cause of mortality associated with cancer, however, our understanding of these processes is insufficient. Metastasis is the end product of a dynamic process in which different interactions between cancer cells and the microenvironment of the organism result in the changes that allow these cells to exceed programmed behavior. Thus, cancer cells spread to new tissues and, ultimately, cause organ dysfunction and death. Understanding the molecular mechanisms involved in the process of metastasis may help to effectively and purposefully prevent and treat cancer metastasis. Attention of the modern researchers aimed at exploring ways to activate thrombosis, coagulation and formation of blood clots, as a prerequisite for metastasis of tumor cells. Sophisticated mechanisms of inducing and coagulation of platelets in combination with the increased activity of the activating vascular endothelial growth factor provide the onset of metastatic foci at a distance from the primary tumor. Learning and development opportunities to block these mechanisms is a promising way to improve the results of treatment of cancer patients. In this review article, we aimed to provide in a concise manner the prospects of studying mechanisms of tumor metastasis , as well as review existing today additional opportunities to optimize the results of treatment of cancer pathology.